Perkembangan dan Peranan Multimedia (Internet) Berbasis Dakwah Islam - Efendi, Erwan; Audia, Alanis; Agung, Muhammad; Widiowati, Nindi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
This research was conducted to find out how the development and role of da'wah-based internet multimedia. The use of research methods seen from the type of research that is using the method used in this research is a qualitative method with a library research approach. The results of this study are the use of multimedia (internet) in preaching including using website facilities, mailing list facilities, chat facilities, blog facilities, social networking facilities. When looking at the current da'wah, it is deemed necessary to evaluate because the media used also influences the implementation and execution of Islamic da'wah. Given the importance of the internet as a means of preaching, it is necessary to use it in preaching related to the use of the internet as a means of conveying da'wah messages. By taking advantage of the current developments, especially multimedia, it is hoped that da'wah will be able to play a role on the internet to convey goodness and solve problems in everyday life. By spreading da'wah through the internet, of course, the scope is wider and can be accepted by a wider audience, both children, young and old. This journal tries to contribute ideas to inspire preachers to use multimedia (internet) as a means of delivering da'wah.